Experiencia de un médico como paciente en un hospital del seguro social del Perú: Physician's experience as a patient in a Peruvian Social Security Hospital - Vega-Pizarro, Raul Enrique (2022)
This paper is an account of the story of a medical patient who contracted COVID-19 and was treated in a Peruvian Social Security Hospital. Doctors, like any other human being, are not free from illnesses, they can fall at the least expected moment and end up in a hospital center as one of the many patients. The hospitalization of a human being leads to the mobilization of all the loved ones, and it is when we get to know the other people, for the hospitalized physician it can at the same time be a stage of self-diagnosis of the doctor-patient relationship.